Learners' Attitude and Motivation in English: ESP Implementation - Hafirah Patang (Ethical Lingua: Journal of Language Teaching and Literature, 2014)
The research aimed at investigating two major problems which have correlation to the implementation of English for Specific Purposes at the computer science study program. They are: (1) the learners' attitude and motivation towards English, and (2) the correlation between the attitude and motivation of learners and their achievement in English.